Network meta-analysis of curative efficacy of different acupuncture methods on obesity combined with insulin resistance - Chen, Jiankun; Gu, Yingming; Yin, Lihong; He, Minyi; Liu, Na; Lu, Yue; Xie, Changcai; Li, Jiqiang; Chen, Yu (Frontiers in Endocrinology, 2022)
Objective: To systematically evaluate the curative efficacy of different acupuncture methods in the treatment on obesity combined with insulin resistance in Randomized clinical trials (RCTs) by network meta-analysis. Methods: Four Chinese database (CNKI, WanFang Data, VIP and SinoMed) and four English database (PubMed, Embase, the Cochrane Library and www.clinicaltrial.gov) were electronically searched for identifying qualified studies. Two reviewers independently screened literature in accordance with inclusion/exclusion criteria by EndNote 20 software and extracted data by ADDIS1.16.8 software, then the risk of bias of included studies were evaluated by Cochrane tool. Network meta-analysis was performed by Stata 15.1 software. The primary outcomes included Fasting blood-glucose (FBG), Fasting serum insulin (FINS), Homeostasis model assessment-IR (HOMA-IR) and Body Mass Index (BMI). The secondary outcomes included Waistline, Waist-hip ratio, Triglyceride (TG), Total cholesterol (TC), High-density lipoprotein (HDL) and Low-density lipoprotein (LDL). Results: 5 RCTs with a total of 410 patients with obesity combined with insulin resistance were included. The results of network meta-analysis showed that compared with control group, three kinds of acupuncture methods (electropuncture, acupoint catgut embedding and acupuncture point patch) had significant efficacy in reducing FBG(electropuncture [MD=-0.44, 95%CI(-0.83, -0.05)], acupoint catgut embedding [MD=-0.36, 95%CI(-0.51, -0.21)]), FINS(electropuncture [MD=-6.17, 95%CI(-9.69, -2.65)], acupoint catgut embedding[MD=-5.87, 95%CI(-6.92,-4.82)], acupuncture point patch [MD=-5.86, 95%CI(-11.40,-0.32)]), HOMA-IR(electropuncture [MD=-1.59, 95%CI(-2.73, -0.45)], acupoint catgut embedding [MD=-0.91, 95%CI(-1.07, -0.75)]), BMI(electropuncture [MD=-1.68, 95%CI(-2.70, -0.66)], acupoint catgut embedding [MD=-3.39, 95%CI(-4.38, -2.40)] and acupuncture point patch [MD=-2.90, 95%CI (-4.93, -0.87)] ) and waistline(electropuncture [MD=-5.49, 95%CI(-8.56, -2.42)] and acupoint catgut embedding [MD=-4.91, 95%CI(-7.51, -2.31)]) in obese patients with insulin resistance, suggesting their efficacy was better than western medicine group in some of the outcome indicators. For the index related to blood lipid, the efficacy of electropuncture was significantly better than behavioral therapy and western medicine. Except that acupoint catgut embedding was superior to electroacupuncture in reducing BMI, there was no statistically significant difference in efficacy among the three acupuncture methods. Conclusions: The results showed that the therapeutic effect of acupuncture methods was superior to conventional western treatment alone, acupuncture methods could serve as a alternative or adjunctive treatment in obese patients with insulin resistance.